Meningkatkan Kemampuan Usaha dan Digital Technology untuk Mengoptimalkan Perekonomian Masyarakat Nahdlatul Ulama Kabupaten Malang - Alexius Endy Budianto; Yuli Ifana Sari; Sri Wilujeng (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
Nahdlatul Ulama in Malang Regency, some of the people are engaged in home-based businesses and are farm Laboure’s. The first problem is semi-finished products that are sold or deposited to collectors so that the added value is low. The second problem is limited production capacity because the production process is done manually or relying on human labor, the third problem is not implementing good business management, not having financial reports, so business development analysis cannot be carried out. The solutions offered are product diversification, namely producing finished products, increasing production capacity by applying technology and digital technology; and the third solution is to increase business management knowledge and skills. The main activities to be carried out include 2 programs: the first is training and mentoring, the second is science and technology substitution. Training and mentoring include training and mentoring in financial management and marketing management. The aim is to provide knowledge and ability to apply simple financial management in the form of business cash flow and business turnover. In addition, target partners are given knowledge and skills about digital technology marketing to optimize their business for the Nahdlatul Ulama community in Malang Regency.